12.8k views
2 votes
2(x + 9) = 4(x - 7) + 2

2 Answers

0 votes

Answer:

x=22

Explanation:

2x+18=4x-28+2

2x+12=4x-26

2x+44=4x

44=2x

22=x

User Coffeduong
by
4.8k points
3 votes

Answer:

x = 22

Explanation:

Step 1: Write equation

2(x + 9) = 4(x - 7) + 2

Step 2: Solve for x

  1. Distribute: 2x + 18 = 4x - 28 + 2
  2. Combine like terms: 2x + 18 = 4x - 26
  3. Subtract 2x on both sides: 18 = 2x - 26
  4. Add 26 to both sides: 44 = 2x
  5. Divide both sides by 2: 22 = x
  6. Rewrite: x = 22

Step 3: Check

Plug in x to verify it's a solution.

2(22 + 9) = 4(22 - 7) + 2

2(31) = 4(15) + 2

62 = 60 + 2

62 = 62

User Noam Yizraeli
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.